Rapport and its managerial implications in FM service outsourcing relationships - Hou, Huiying; Ho, Daniel Chi Wing (International Journal of Strategic Property Management, 2015)
In Hong Kong, client companies tend not to renew contracts with relationship partners and may change facilities management (FM) service providers on a frequent basis. This phenomenon is common in the FM industry. Inspired by the phenomenon of changing service providers, this study sheds light on a social relations perspective in outsourcing relationships and aims to investigate the factors that affect FM service outsourcing relationships. Open interviews with 20 FM managers were conducted, and the interview results were analysed with content analysis and coding methods. The empirical findings were interpreted on two levels. First, FM managers believe that rapport is an influential factor that affects FM service outsourcing relationships. Second, the courses in which the interviewees explain the manifestation of rapport and its significance reveal that common goals, shared values, trust, openness, and coordination are the factors that not only nurture the formation of rapport, but also have significant influences on social relations in the process of outsourcing. A framework has been developed to describe the conceptual relationships found in the empirical findings from the interviews. Eight guidelines have been outlined to indicate the managerial implications of this study.First Publish Online: 19 Jun 2015